Perception and preferences of second professional undergraduate medical students for pharmacology teaching: a questionnaire based cross-sectional study - Kumar, Jeetendra; Pandit, Mrityunjay K.; Anand, Piyush; Kumar, Brajesh (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Feedback from students provides an opportunity to assess lacunae in current systems of teaching and forms the basis for framing desired modifications in the teaching methodology to enhance the magnitude of learning. This study was undertaken to know the views of students on current methodology of pharmacology teaching and to delineate the required changes to be made in it. Methods: The questionnaire based cross-sectional study was conducted on 167 students of second professional undergraduate medical students. The questionnaire was divided in 2 different parts. Part A consisted 20 multiple choice questions on perception and preferences of students for pharmacology teaching and opinion on changes to be made was taken in the part B of the questionnaire. Results: Pharmacology was marked as one of the most interesting and useful subjects by 49.1% and 67.06% of students respectively. Central nervous system (19.76%) and endocrinology (17.96%) were two most boring systems. The central (35.92%) and autonomic (31.73%) nervous systems were two most difficult systems to understand. The combination of lecture notes and textbooks was the preferred reading materials of 58.68% of students. The most preferred teaching media was the combination of blackboard and chalk with power point presentation (80.24%). Increased use of figures, flow charts and diagrams, inclusion of more clinical examples and interactive classes were marked as suggested reforms to enhance the outcome of lecture classes. Conclusions: This study revealed that students are in favour of a substantial change in the current teaching methodology of pharmacology in place of outdated and useless methods.